The Impact of COVID-19 Pandemic Information on Sectoral Stock Performance during Lockdown and New-Normal: An Evidence from Indonesia Stock Exchange - Nusantara, Fariz Junior (AIBPM Publisher, 2021)
The Indonesian economy has weakened in every sector since pandemic Covid-19. The study investigates how the stock return in the impacted and unimpacted industry reacts to death and cases information about Covid-19. Based on previous studies, behavioral changes also occur in society. Changes in consumption of mass products and also the behavior of fast-food products move in opposite directions. In addition, changes also occur in employee performance due to limitations related to activities. In addition, this study also considers the response from the Indonesian government regarding changes in people's behavior and the increase in cases related to Covid-19. The Indonesian government, in this case, implemented several policies as a response to the incident where the Indonesian government finally imposed restrictions on social activities followed by a transition period to maintain the economic cycle in Indonesia. This study shows that in both the impacted and unimpacted industries and the lockdown period and the new-normal period in the Indonesian version, information related to the Covid-19 case significantly negatively affected stock returns, while information on deaths due to Covid-19 has a negative effect that is not significant. This result suggests the practitioner considers which other information affects investment decision during the Pandemic in the future.